Human Security di Papua pada Masa Pemerintahan Jokowi: Tinjauan terhadap Political Security di Papua - Ignatius Yonatan (Jurnal Sentris, 2018)
The continuing conflict in Papua is a problem that should be given more attention by the current Indonesian government. The problem is not merely a matter of integrity, and economy. However, it is also about human security’s matter, especially, political security in Papua. Until now, Papuans still face different treatment than those in other parts of Indonesia. Violence and abuse of human rights, also other form of cruelty still happen there. As president of Indonesia, Jokowi is expected to be able to solve the political security’s matter in Papua. However, it should be admitted that solving political security’s matter in Papua is not that easy. Nevertheless, Jokowi has shown good intentions to restore Indonesia’s relations with Papua through economic approach. This research will discuss about how human security in Papua under Jokowi with focus on the review of political security in Papua.